Echoes the series : afro- asian literature 8 - Salvosa, Auxilie Aurora D. (Valenzuela City : Jo-es Publishing House, Inc., 2020)
"Echoes the series is a response to the growing needs of teachers and students to come up with materials that do not only aid in the development of communicative competence and proficiency in the use of English language, but also make learning holistic and enjoyable."
Includes glossary and references.
English text.
Keywords: Philippine literature -- Collections; Literature & rhetoric